Retina and Omega-3 - Giuseppe Querques; Raimondo Forte; Eric H. Souied (Journal of Nutrition and Metabolism)
Over the last decade, several epidemiological studies based on food frequency questionnaires suggest that omega-3 polyunsaturated fatty acids could have a protective role in reducing the onset and progression of retinal diseases. The retina has a high concentration of omega-3, particularly DHA, which optimizes fluidity of photoreceptor membranes, retinal integrity, and visual function. Furthermore, many studies demonstrated that DHA has a protective, for example antiapoptotic, role in the retina. From a nutritional point of view, it is known that western populations, particularly aged individuals, have a higher than optimal omega-6/omega-3 ratio and should enrich their diet with more fish consumption or have DHA supplementation. This paper underscores the potential beneficial effect of omega-3 fatty acids on retinal diseases.